Entrepreneurship and globalization - Bell, Jim , 1954-; McNaughton, Rod B. (Contemporary issues in business and globalization, 2009)
An important set, this collection draws together earlier literature on small and medium enterprise export development and internationalization from disparate sources into a cohesive body of work, which traces the evolution of our understanding of the topic.